PERAN PEMBERDAYAAN DALAM MENOPANG KREATIVITAS SUMBER DAYA MANUSIA SEBAGAI SUMBER DAYA SAING INDUSTRI KECIL DAN MENENGAH (IKM) DI KABUPATEN BADUNG PROVINSI BALI - Desak Ketut, Sintaasih; Ni Nyoman, Kertiyasa; Ni Wayan, Mujiati; Indrawati, Ayu Desi (PIRAMIDA, 2014)
Small and medium industry (SMI) is the leading sector of the economy of Bali that have contribution on export and labor absorption. In the face of the increasingly competition nowadays, SMI should have primacy as a typical company’s ability to win the competition. The purpose of this research is to know the application of empowerment of human resources and its role in the creativity of employees as a source of competitiveness of the company. Responden in this research are employees of SMI apparel industry sectors from textiles and craft industry of wood, metal, gold and silver, in the Badung Regency. These studies use quantitative analysis approach, using multiple linear regression analysis technique. The results showed that the structural and psychological empowerment simultaneously significant role in propping up the creativity of employees. Structural and psychological empowerment partially also plays a positive and significant in the creativity of employees. The results of this research may imply that the better structural and psychological empowerment happens in companies growing the SMI creativity of employees. The creativity demonstrated by the new combination makes creative in completing the work and improve the ways of completing tasks so that the results of its work more meaningful for the company in the face of an increasingly tight competition.
Keywords: Structural empowerment; psychological empowerment; creativity